Design and analysis of lightweight and robust authentication protocol for securing the resource constrained IIoT environment - Ahmed Mohammed Alghamdi (PLoS ONE, 2025)
The Internet of Things (IoT) is a vast network of devices, sensors, wearables, or any other object capable of processing, storing, sending, and receiving data over an open network channel. This versatility gives IoT numerous applications, one of them being in the industry, also known as the Industrial Internet of Things (IIoT). As IIoT relies on an open network channel for data sharing, it is vulnerable to numerous threats, including side channels, impersonation attacks, and clock synchronization issues for which device authentication becomes crucial. Researchers occasionally proposed numerous authentication protocols using conventional cryptographic methods, identity-based cryptographic techniques, or certificateless methods; however, these protocols either suffer from modular exponentiation partial private key distribution problems or are completed in four to five round-trips during authentication. Therefore, this article presents an Elliptic Curve Cryptographic (ECC)-based efficient technique that emerges as a significant solution, addressing the certificate revocations, overheads problem, and the partial private key distribution problem of identity-based cryptography, respectively. The security of the proposed ECC-based protocol is of utmost importance in addressing all the known vulnerabilities in IIoT, freeing the industrial system from the urgency and the issue of data breaches. Its potential to instil a sense of security and confidence in IIoT deployment is crucial in improving user trust. Upon comparing the proposed protocol with state-of-the-art schemes, the result demonstrated that the proposed protocol enhanced 51.44% in terms of communication costs and 91.88% in terms of computation costs. So, it is recommended for practical implementation due to its fast and provable secure nature, making the industry feel confident and safe about its implementation.